A Study Guide to The Fabric of Reform. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This guide is designed to facilitate classroom use of The Fabric of Reform, a 30-minute educational video created by the International Monetary Fund. It is intended for use with students in economics and international relations courses at the secondary and postsecondary levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet